Proximity is not access: A capabilities approach to understanding non-motorized transport vulnerability in African cities - Cooke, Sean; Ryseck, Bianca; Siame, Gilbert; Nkurunziza, Alphonse; Molefe, Lerato; Zuidgeest, Mark (Frontiers in Sustainable Cities, 2022)
A paradigm shift regarding the fundamental premise of transport planning is underway. The objectives of shifting to accessibility-based planning includes changing the focus of transport planning practices from speed to access, from the system to the user, and from efficiency to equity. However, despite equity as a stated aim, many approaches to access planning fail to question an inequitable, often subconscious, belief at the core of transport planning: that proximity is access. But, for many groups of people in our society, proximity to public transport does not mean affordability, proximity to services does not mean disability-friendly, proximity to destinations does not mean personal safety; proximity is not the same as access. To explore this disjuncture between proximity and access for those vulnerable people groups, and what it means for transport planning, this study utilises a less conventional conceptualisation of access, one in terms of the capabilities approach. This framework, along with a series of semi-structured interviews, is used to better understand the nature and consequences of access deprivation on vulnerable young non-motorised transport users in three African cities, and its implications for transport planning practice. The research finds that, despite the theoretical access that the participants have, to amenities, services, employment opportunities and transport infrastructure, through proximity, their actual set of viable access options is constrained much further by factors outside of the remit of transport planning. The positivist nature of transport planning, and the reliance on quantitative data collection methods, hides the true cost burden of access deprivation for the most vulnerable transport users. The unseen cost burden being the trips that are not taken, the trips that cannot be taken despite the proximity of the destination, and the effect of those unrealised trips on a vulnerable person's freedom to access the opportunities that will improve their livelihood. Desire, intention, need, vulnerability, and capability are all vitally important characteristics of access that are largely invisible in current quantitative datasets, especially for those whose access is most fragile, vulnerable non-motorised transport users. A ‘just transition’ from mobility-based to access-based transport planning needs to incorporate a combination of mixed-method transport practices.